Replication-transcription complex of coronaviruses: functions of individual viral non-structural subunits, properties and architecture of their complexes - E. L. Mishchenko; V. A. Ivanisenko (Вавиловский журнал генетики и селекции, 2022)
Coronaviruses (CoVs) belong to the subfamily Orthocoronavirinae of the family Coronaviridae. CoVs are enveloped (+) RNA viruses with unusually long genomes. Severe acute respiratory syndrome CoV (SARS-CoV), Middle East respiratory syndrome CoV (MERS-CoV), and the novel coronavirus (2019-nCoV, SARS-CoV-2) have been identif ied as causing global pandemics. Clinically tested vaccines are widely used to control rapidly spreading, acute, and often severe infections; however, effective drugs are still not available. The genomes of SARS-CoV-2 and SARS-CoV are approximately 80 % identical, while the genomes of SARS-CoV-2 and MERS-CoV are approximately 50 % identical. This indicates that there may be common mechanisms of coronavirus pathogenesis and, therefore, potential therapeutic targets for each virus may be the same. The enzymes and effector proteins that make up the replicationtranscription complex (RTC) of coronaviruses are encoded by a large replicase gene. These enzymes and effector proteins represent promising targets for potential therapeutic drugs. The enzyme targets include papain- and 3C-like cysteine proteinases that process two large viral polyproteins, RNA-dependent RNA polymerase, RNA helicase, viral genome-modifying enzymes, and enzymes with 3’–5’ exoribonuclease or uridylate-specif ic endonuclease activity. Currently, there are many studies investigating the complex molecular mechanisms involved in the assembly and function of the RTC. This review will encompass current, modern studies on the properties and complexes of individual non-structural subunits of the RTC, the structures of individual coronavirus RTC subunits, domain organization and functions of subunits, protein-protein interactions, properties and architectures of subunit complexes, the effect of mutations, and the identif ication of mutations affecting the viability of the virus in cell culture.